2014
DOI: 10.13171/mjc.3.5.2014.10.14.23.44
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial and antifungal activities of the Cedrus atlantica (Endl.) Manettiex Carrière seeds essential oil

Abstract: The Atlas cedar is an endemic species of the African North Mountains. The goal for which this work was conducted is to determine the chemical composition and to study the antibacterial and the antifungal activity of the hydrodistilized essential oil from both the winged and wingless seeds of the High Atlas Cedrus atlantica (Morocco). The essential oil is analyzed by gas chromatography and gas chromatography mass spectrometry. The essential oil yields of winged as well as wingless seeds were respectively 2.6% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
3
19
1
Order By: Relevance
“…This information is coherent with assertion of R. Rhafouri et al, (2014) [22]. Results depicted in figure 4, showed that men (69%) are more knowledgeable than women (31%) about traditional phytotherapy.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This information is coherent with assertion of R. Rhafouri et al, (2014) [22]. Results depicted in figure 4, showed that men (69%) are more knowledgeable than women (31%) about traditional phytotherapy.…”
supporting
confidence: 89%
“…Men are used to collect medicinal plants from dangerous places therefore they benefit from these plants to relieve pain and remain healthy. This observation has also been made at a national scale by other authors in their ethnobotanical studies [22].…”
supporting
confidence: 75%
“…Satrani et al [ 43 ] also concluded that C. atlantica essential oil has antimicrobial activity against Escherichia coli, B. subtilis , Micrococcus luteus , and Staphylococcus aureus . A similar study demonstrated that the essential oils derived from Atlas cedar winged and wingless seeds were able to inhibit the growth of Escherichia coli at a concentration of 1/100 v / v [ 44 ]. C. atlantica essential oil in our study showed weak antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…This is slightly higher than that obtained by the steam stripping distillation (2,4%) reported by Aberchane et al 2001. The yields of Cedar wood essential oil varies greatly depending on the forest source (Aberchane et al 2004), and the part of tree used (Derwich et al 2010, Rhafouri et al 2014. Indeed, distillation needles yielded about 1,8 % while the seeds gave yields between 2,6 and 3,6% (Derwich et al 2010).…”
Section: Chemical Composition Of Cedrus Atlantica Wood Essential Oilmentioning
confidence: 99%
“…While the major components of the essential oil of the non-winged seeds were α-pinene (46,16%), manool (25,47%), bornyl acetate (10,18%), β-pinene (5,95%) and α-terpinene (2,71%), those of winged seeds essential oil were manool (49,02%) , α-pinene (40,82%), 6-comphenol (2,52%) and β-pinene (2,13%) (Derwich et al 2010, Rhafouri et al 2014. Essential oils extracted from small branches of C. atlantica originated from different localities of Corsica were also dominated by α-pinene (up to 79,4%), himachalol (up to 66,2%), β-pinene (up to 21,49%), β-himachalene (up to 19,3%), γ-himachalene (up to 11,0%), and α-himachalene (up to 10,9%) (Paoli et al 2011).…”
Section: Chemical Composition Of Cedrus Atlantica Wood Essential Oilmentioning
confidence: 99%